Risk of Vitamin D Deficiency in Smokers: Mix-Method - Amelia Lorensia; Marthy Meliana Ariyanti Jalmav; Zahwa Dhiba; Rivan Virlando Suryadinata (Faculty of Public Health, Hasanuddin University, Makassar, 2024)
Cigarettes are one of the leading causes of death in the world and Indonesia. Cigarettes emit cigarette smoke, which contains toxins and has pro-inflammatory properties that interfere the metabolism of vitamin D in the lungs. The study aimed to determine the risk of vitamin D deficiency in active smokers in Rungkut Village, Surabaya City. This research method is a mix-method with a Convergent Parallel Design type strategy, which is a way of collecting quantitative (cross-sectional) and qualitative data (interpretative phenomenological analysis) simultaneously, with purposive sampling technique. The variable was the risk of vitamin D deficiency and vitamin D level. Subjects were active smokers aged ≥19 years in the Rungkut Subdistrict. The number of samples involved in this research was 125 samples in the quantitative phase, and 15 people in the qualitative phase. The highest level of smoking severity was light smokers (45.60%). Most of respondents had normal vitamin D levels (≥20 mg/mL) of 73.33%, averaging of 37.66 ± 5.89 mg/mL. Most active smokers are at risk of vitamin D deficiency. Risk factors for deficiency in heavy smokers are not consuming foods containing vitamin D (such as fish, eggs, and milk), not consuming fish oil supplements and vitamins, and not sunbathing. However, the level of physical activity tended to be moderate-heavy. The conclusion is that smokers must pay attention to their intake of foods containing vitamin D and exposure to sunlight to achieve sufficient vitamin D levels.